Antimicrobial activities of actinomycetes isolated from Malaysian tropical mangrove forest of Kuantan, Pahang - Zainal Abidin, Zaima Azira; Abdul Malek, Nurfathiah; Chowdhury, Ahmed Jalal Khan; Zainuddin, Zarina (2016)
Actinomycetes, a group of slow growing, Gram positive bacteria belonging to the order of Actinomycetales are widely distributed in nature. They are biotechnologically important for their renowned capability to produce various bioactive secondary metabolites. Isolation and screening from poorly explored habitat offers a promising natural source of bioactive actinomycetes. This study aimed to assess the diversity of actinomycetes from mangrove sediments of Kuantan, Pahang and evaluate their potential for the production of antimicrobial secondary metabolites. A total of 100 representative isolates were selected for further investigation from a collection of 3484 isolates recovered from 5 different sampling sites using various isolation procedures. The antimicrobial potential of the representative isolates were preliminary assessed using the cross streak method against Bacillus subtilis, Candida albicans, Escherichia coli, Serratia marcescens and Staphylococcus aureus. Approximately 53.0 % of the total isolates possessed antimicrobial potential against at least one of the test organisms. The crude ethyl acetate extract of these bioactive isolates were further evaluated using disc diffusion method, in which 26.4% (n=14) isolates exhibited inhibitory activity against more than half of the test organisms. Streptomyces sp. K1-01 and Streptomyces sp. K2-03 demonstrated broad spectrum of antimicrobial activity against all test organisms, indicating that genus Streptomyces could provide high quality metabolites for drug discovery. Fourteen selected bioactive isolates were screened for biosynthetic genes encoding the non-ribosomal peptide synthetases (NRPS) and polyketide synthases type I (PKS-I). The NRPS and PKS-I gene were detected in 50.0% and 71.4% of the total isolates, respectively. Six isolates exhibited the presence of both NRPS and PKS-I genes, of which 4 isolates belong to genus Streptomyces and another 2 isolates belong to genus Micromonospora. The occurrence of NRPS and PKS-I genes provides an early evaluation on their biosynthetic capabilities. Mangrove actinomycetes enumerated in this study demonstrated high level of diversity as the 33 isolates chosen for phylogenetic analysis using 16S rRNA gene sequences were distributed among 9 genera. Streptomyces and Micromonospora are the most predominant genera observed; alongside Micrococcus, Gordonia and Nocardia. Besides, this is the first report describing the isolation of Dietzia, Pseudonocardia, Saccharopolyspora and Verrucosispora from Malaysian mangrove sediments. In conclusion, Malaysian mangrove ecosystem has the potential as an important reservoir of actinomycetes for the discovery of antimicrobial secondary metabolites